LEGAL REGULATION OF THE OPERATION OF UNMANNED AVIATION COMPLEXES IN PERFORMING THE TASKS OF THE NATIONAL POLICE OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article provides an analysis of the regulatory framework that regulates the application and use of unmanned aircraft, unmanned aerial vehicles and unmanned aircraft systems, and provides an assessment of the regulatory support for the operation of unmanned aircraft systems in the performance of tasks assigned to the National Police of Ukraine. The authors provide statistical data on the growth of the field of use of unmanned aircraft systems in the world, elaborate modern trends and vectors of development of this field in Ukraine, provide comments of the military and political leadership of Ukraine on this issue. The authors present the results of international research on the possible injury of people in the event of accidents involving unmanned aircraft. The article outlines the retrospective of state regulation of new industries and, on their example, outlines the prospects for regulatory and legal regulation of the application and use of unmanned aircraft systems in Ukraine as a whole, and when performing the tasks of the National Police of Ukraine - directly. The authors analyzed the current state of regulatory and legal support and methods of state regulation of the operation of unmanned aircraft complexes, the procedure for registering unmanned aircraft and obtaining documents giving the right to pilot unmanned aerial vehicles. Separately analyzed regulatory acts regulating the application and use of unmanned aircraft systems in the performance of tasks of the National Police. The requirements for external pilots of unmanned aircraft complexes are analyzed, an assessment of the set of skills and abilities that an external pilot must possess, as well as methods of obtaining documents confirming the status of an external pilot, are provided. The requirements of state aviation regarding the organization and conduct of flights, as well as the preparation of relevant documentation, were analyzed and relevant conclusions were provided.
Keywords: UAV; National Police; regulatory; operation; unmanned aviation